Critical potential of early cardiac surgery for infective endocarditis with cardio-embolic strokes. (15th January 2017) - Suzuki, Makoto; Takanashi, Shuichiro; Ohshima, Yutaro; Nagatomo, Yuji; Seki, Atsushi; Takamisawa, Itaru; Tobaru, Tetsuya; Naito, Kazuhiro; Kin, Hajime; Umemura, Jun; Takayama, Morimasa; Sumiyoshi, Tetsuya; et al.
Abstract: Background: Early cardiac surgery may have a trade-off between stabilized hemodynamics with controlled infection and a risk of peri-operative death in patients with infective endocarditis (IE) complicated with cardio-embolic strokes. Methods: We retrospectively studied clinical characteristics and outcomes in 68 consecutive patients with IE (mean age, 58 ± 3 years, 62% male) who admitted in our institute during June 2013 and August 2015. Results: Cardio-embolic strokes were noted in 37% of patients (n = 25) with IE and overall in-hospital mortality was 4 times higher in IE with cardio-embolic strokes than IE with an absence of strokes (n = 43) (20% vs. 4.7%, p = 0.045). Bacteremia of Staphylococcus aureus (p = 0.021) and a complication of cardio-embolic strokes (p = 0.031) were independently associated with in-hospital death in those with IE. However, in-hospital mortality was quite low in 19 with early cardiac surgery compared with 6 with conventional treatment in those with cardio-embolic strokes (11% vs. 50%, p = 0.035). Multivariate logistic analysis demonstrated that lack of early cardiac surgery (p = 0.014), a complication of cerebral hemorrhage (p = 0.002), and a presence of refractory heart failure (p = 0.047) were independently associated with in-hospital death in those with IE complicated with cardio-embolic strokes. Conclusion: Early cardiac surgery may provide clinical advantages overcoming peri-operative risks in those with IE complicated with cardio-embolic strokes.